2014
DOI: 10.1136/oemed-2013-101874
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal effects of air pollution on exhaled nitric oxide: the Children's Health Study

Abstract: OBJECTIVES To assess the effects of long-term variations in ambient air pollutants on longitudinal changes in exhaled nitric oxide (FeNO), a potentially useful biomarker of eosinophilic airway inflammation, based on data from the southern California Children’s Health Study. METHODS Based on a cohort of 1,211 schoolchildren from 8 Southern California communities with FeNO measurements in 2006/07 and 2007/08, regression models adjusted for short-term effects of air pollution were fitted to assess the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 44 publications
5
43
0
2
Order By: Relevance
“…26 Additionally, data from the Southern California Children's Health Study have shown that increases in annual average exposure to ambient air pollutants, such as NO2 and PM2.5, are significantly associated with increased FeNO in children, independent of short-term exposure to ambient air pollution and asthma status. 27 FeNO levels have been correlated with personal and ambient air pollution in children with asthma. 28 In 2 pollutant models, FeNO levels were strongly positively associated with personal and ambient elemental carbon and NO2, and with personal, but not with ambient PM2.5.…”
Section: Environmental Factors 1) Outdoor Air Pollutionmentioning
confidence: 99%
See 3 more Smart Citations
“…26 Additionally, data from the Southern California Children's Health Study have shown that increases in annual average exposure to ambient air pollutants, such as NO2 and PM2.5, are significantly associated with increased FeNO in children, independent of short-term exposure to ambient air pollution and asthma status. 27 FeNO levels have been correlated with personal and ambient air pollution in children with asthma. 28 In 2 pollutant models, FeNO levels were strongly positively associated with personal and ambient elemental carbon and NO2, and with personal, but not with ambient PM2.5.…”
Section: Environmental Factors 1) Outdoor Air Pollutionmentioning
confidence: 99%
“…There are some inconsistent results with regard to the study population (i.e., atopic vs nonatopic and asthmatic vs nonasthmatic), treatment (i.e., naïve asthma vs after corticosteroid treatment), asthma condition (i.e., asthma controlled vs uncontrolled and stable asthma vs during asthma exacerbation), and various levels of exposure (i.e., personal vs ambient exposure, level of exposure, and short term vs long term exposure). 27 Therefore, further research on the usefulness of FeNO to identify the adverse respiratory effects of the exposure to pollutants in children is needed.…”
Section: Environmental Factors 1) Outdoor Air Pollutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Th ough not specifi c for air pollution exposure, biomarkers with the potential for future clinical application include exhaled nitric oxide, micronuclei frequency in buccal mucosa cells, microRNA in induced sputum samples, malondialdehyde in exhaled breath condensate, and serum IL-6 levels. 37,[55][56][57][58] Of the ILDs, IPF, in particular, is age-related, raising the possibility that lifetime cumulative environmental exposures may relate to the advanced cellular senescence seen in this disease. 23,59 Comprehensively characterizing the environmental contributors to fi brogenesis (either directly or through gene and environment interactions) may be an essential step in understanding the complex pathobiology of IPF.…”
Section: Integrating Environmental Exposures Into Disease Models: Th mentioning
confidence: 99%